Modeling of the catalytic reforming process with a fixed catalyst bed based on industrial data - Zhakmanova, Yekaterina; Dyussova, Rizagul; Seitenova, Gaini; Borashova, Moldir (International Journal of Innovative Research and Scientific Studies, 2025)
This study presents the development of a mathematical model for the simulation and analysis of the catalytic reforming process using a Python-based software tool. The model captures the kinetics of hydrocarbon feedstock processing within a fixed catalyst bed, ensuring a balance between accuracy and computational efficiency. A key feature of the software is a digital flow diagram that visualizes material and energy flows at each stage of the process while displaying critical parameters such as temperature, pressure, and flow rate. To validate the model's accuracy, the calculated data were compared with experimental values obtained from commercial fixed-bed reforming units. The results showed an absolute calculation error of no more than 3%, confirming the model’s reliability in accurately describing reforming processes. Furthermore, the study investigates the effects of temperature and pressure variations on the final product yield to enhance process efficiency and optimize operating conditions.